THE REPRESENTATION OF CULTURES IN AN ENGLISH TEXTBOOK - Aufa, Wahidatul; Ririn Pusparini (STKIP Siliwangi, 2024)
Textbooks are essential for teaching and learning English. Cultural material is important in English textbooks since language and culture are inseparably linked. Curriculum changes are common in the Indonesian educational system, prompting textbook modifications, including those for English language materials. Recognizing that each textbook has unique advantages and limitations, this study investigates the cultural categories offered in the English textbook BRIGHT. It also tries to determine the primary cultural characteristics featured in this textbook. The study used a content analysis methodology, which involved carefully reviewing the textbook's material using an observation sheet. This study utilizes a qualitative design, focusing on textbook content analysis and documenting results as percentages. The findings show that the textbook focuses on source cultures with insufficient representation of target cultures. This limited representation emphasizes the need for better equal incorporation of cultural elements. The textbook is considered appropriate for Indonesian students since it follows important standards that advocate for the inclusion of both source and target cultures, making the material more relevant and improving cultural understanding and language abilities required for global communication.